Knowledge, skills, access and usage status of computers, internet and databases in nursing students and some of the related factors - Saeidi, Maryam; Jafari manesh, Hadi; Yaghmaei, Farideh; Ranjbaran, Mehdi; Godarzvand, Laleh; Hariri, Gholamreza; Imanzad, Masoumeh (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim. Today, medical and nursing education is moving from traditional into student-centered educational system. In this context, teaching and learning via computers and internet has been increasing in popularity. This study was aimed to determine the knowledge, skills, access and usage of computers, internet and databases in nursing students and some of the related factors. Materials and Methods : This is a descriptive and correlation study. 145 undergraduate students were randomly selected from the nursing midwifery school. Data were collected by “status of computer and internet usage” questionnaire. Content validity and test-retest method were used for its validity and reliability respectively. Data were analyzed by SPSS version 20 and analytical - descriptive statistics. Results: Nursing students expressed their knowledge and skills of computers and internet usage in the good level. Also, their access to computers and internet were “high” (44. 8%) and “moderate” (47. 6 %) respectively. The most important factors of facilitating and inhibiting usage of computers and internet were “Easy using of computer” and “Slow speed of internet” respectively. The knowledge and skills of computers and internet usage was correlated with their usage. Conclusions: The results of this study highlights needs of computers and internet learning for nurses. This should be consider by health planners and policy makers. Keywords: Computers, Internet, Databases, Nursing Students REFERENCES Abtahi S Feali M (2008)[ Evaluation of skill and use of Information Technology and Internet among professors, postgraduate and undergraduate students in Mashhad Dental School in Iran in 2007-2008]. Journal of Mashhad Dental School . 32(4) 257-262. (Persian) Applebee A Clayton P Pascoe C Bruce H (2000) Australian academic use of the Internet: implications for university administrators. Internet Research . 10(2) 141-149. Isman A Dabaj F (2003) Attitudes of students towards Internet. World Conference on E-Learning in Corporate, Government, Healthcare, and Higher Education. Jacobs HL (2008) Information literacy and reflective pedagogical praxis. The journal of Academic Librarianship . 34(3) 256-262. Jetté SD Tribble SC Gagnon J Mathieu L (2010) Nursing students’ perceptions of their resources toward the development of competencies in nursing informatics. Nurse Education Today . 30(8) 742-746. Kalsman MW Acosta DA (2000) Use of the Internet as a medical resource by rural physicians. The Journal of the American Board of Family Practice . 13(5) 349-352. Kumar ST Tadakamadla J Tibdewal H et al (2010) Internet usage among undergraduate dental students in India. Revista Odonto Ciência. 25(3) 261-265. Layfieldk Dk Radhakrishna, RB, & Scanlon, DC, (1999), An assessment of Pennsylvania secondary agriculture teachers, perceptions of and use Internet. Journal of Southern Agriculture Education Research . 50(1) 48-55. Maleki Z Goudarzi M Mohtashami L Faghihi B (2010) [Knowledge and attitudes of dental students and academic staffs towards internet usage in dental training in Shahid Beheshti University of Medical Sciences]. Journal of Dental School Shahid Beheshti University of Medical Sciences . 28(1) 40-47. (Persian). Mokhtari noori J Zahri S Yaghmaee F et al (2011)[ Study of factors related to internet use with usage of internet by teachers according to Theory of Reasoned Action. Iranian Journal of Nursing Research . 5(19) 25-36. Movahed Mohammadi H Irvani H (2002) Patterns of internet use by students of the faculty of agriculture of Iran. Iranian Journal of Agriculture Sceince . 33(4) 717-727. Park H (2004) Factors that affect information technology adoption by teachers. Retrieved 2014, from http: //digitalcommons. unl. edu/dissertations/AAI3126960/. Phillips R (2000) Handbook for Learning-centred Evaluation of Computer-facilitated Learning Projects in Higher Education. Retrieved 2014, from http: //cleo. murdoch. edu. au/evaluation/survey/itsurvey/html. Rajab LD Baqain ZH (2005) Use of information and communication technology among dental students at the University of Jordan. Journal of Dental Education . 69(3) 387-398. Rastgoo A Naderi E Shariatmadari A Seifnaraghi M (2010) [The Impact of Internet Information Literacy Training on University Student’s Problem]. Quarterly Journal of New Approaches in Educational Administration . 1(4) 1-22. (persian). Ray K Day J (1998) Student attitudes towards electronic information resources. Information research . 4(2) 4-2. Sajadi FS Shokoohi M Kakoei S Sheikhi F (2013)[ Evaluation of skills and use of computer and internet among professors, postgraduate and undergraduate students in Kerman, Iran]. Strides in Development of Medical Education . 10(2) 47-55. (Persian). Scott SD Gilmour J Fielden J (2008) Nursing students and internet health information. Nurse Education Today . 28(8) 993-1001. Tavassoli, M, Lak Bala, P, & Zare, S, (2002), The use of internet and other sources among physicians in Hormozgan University of Medical Sciences for their professional updating, 2001. Journal of Hormozgan University of Medical Sciences 6(2), 37-33. Tsai CC (2004). Adolescents’ perceptions toward the internet: A 4-T framework. CyberPsychology & Behavior . 7(4),458-463. Uribe, S, & Mariño, R, (2006), Internet and information technology use by dental students in Chile. European Journal of Dental Education . 10(3), 162-168. Walmsley A D White D A Eynon R Somerfield L (2003) The use of the Internet within a dental school. European Journal of Dental Education . 7(1) 27-33. Yaghoubi J Shamsai E (2004), Assessing effective factors in using Internet by faculty members of Agricultural College of Zanjan University, Iran. Proceedings of the 19th Annual Conference Dublin, Ireland,(2004, May).